2014
DOI: 10.1155/2014/931740
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Audible Sound Control on Mung Bean (Vigna radiate) Sprout

Abstract: Audible sound (20–20000 Hz) widely exists in natural world. However, the interaction between audible sound and the growth of plants is usually neglected in biophysics research. Not much effort has been put forth in studying the relation of plant and audible sound. In this work, the effect of audible sound on germination and growth of mung bean (Vigna radiate) was studied under laboratory condition. Audible sound ranging 1000–1500 Hz, 1500–2000 Hz, and 2000–2500 Hz and intensities [80 dB (A), 90 dB (A), 100 dB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…2, we noted that sound stimulation evidently promoted the growth of E. coli K-12. Cai et al (2014) reported that the germination period of mung beans was reduced after audible sound treatments with 1.0–2.5 kHz. The PO algae under exposure of sound waves with frequency of 2,200 Hz had greatly significant increase in dry biomass (Cai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2, we noted that sound stimulation evidently promoted the growth of E. coli K-12. Cai et al (2014) reported that the germination period of mung beans was reduced after audible sound treatments with 1.0–2.5 kHz. The PO algae under exposure of sound waves with frequency of 2,200 Hz had greatly significant increase in dry biomass (Cai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2, we noted that sound stimulation evidently promoted the growth of E. coli K-12. Cai et al (2014) reported that the germination period of mung bean was reduced after audible sound treatments with 1.0-2.5 KHz. And the PO algae under exposure of sound waves with frequency of 2200 Hz had greatly significant increase in dry biomass (Cai et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This system was assembled using an incubator clamp on a 1585 orbital shaking incubator (VWR, PA, USA). [2] beaker, [3] plastic supporter, [4] speaker, [5] sound generator, [6] flexible tubing, [7] sample receiver, [8] flask swab, [9] lid with two outlets, [10] syringe, [11] 0.45 mm filter, [12] tweezers, [13] cotton. bottle cap [9]; on the second outlet, a syringe [10] with a 0.45 mm filter [11] was attached to generate a pressure difference so that the sample could move from the flask to the beaker.…”
Section: Sound Induction Devicementioning
confidence: 99%
“…This knowledge may eventually lead to the development of technology in fields such as applied microbiology, bioengineering, agroindustry and medicine. Although there have been scientific reports describing the effects of sound on living organisms, especially plants, [1][2][3][4] there are few studies addressing how sound affects unicellular organisms.…”
Section: Introductionmentioning
confidence: 99%